Transcriptomic analysis of profibrinolytic and fibrinolytic inhibitor genes in COVID-19 patients - Febrianti, Ika K.; Putra, Andani E.; Raveinal, Raveinal; Elliyanti, Aisyah (Narra J, 2024)
The immunopathogenesis of COVID-19 infection is initiated by the entry of the SARS-CoV-2 virus into the human body through droplets, entering the lungs and binding to the ACE-2 receptor. Activated macrophages stimulate an immune and inflammatory response, leading to the activation of the coagulation cascade, including profibrinolytic and fibrinolytic inhibitor processes. One of the proteins involved in profibrinolytic is encoded by the PLAUR gene, while fibrinolytic inhibitor proteins are encoded by the A2M and SERPINE1 genes. This research aims to assess the transcriptomic analysis of genetic expression data of profibrinolytic genes, fibrinolytic inhibitor genes and their correlation with serum D-dimer levels, which describe the clinical condition of coagulation in COVID-19 patients. This cross-sectional study included 25 patients each for mild and moderate-to-severe COVID-19 at Dr. M. Djamil Padang General Hospital, Padang, Indonesia. Inter-group gene expression comparisons will be analyzed using log2 folds change, and bivariate tests will be analyzed using correlation. The results show that the PLAUR gene has higher expression in moderate-to-severe compared to mild cases. Similarly, the SERPINE1 and A2M genes expressions are higher in moderate-to-severe compared to mild cases. Furthermore, there is a significant correlation between serum D-dimer levels and profibrinolytic factor (PLAUR gene) expression in COVID-19 patients. The correlation between serum D-dimer levels with fibrinolytic inhibitor factor (SERPINE1 and A2M genes) expression was found. These conclude that there is a significant difference in the expression of the profibrinolytic and fibrinolytic inhibitor genes between mild and moderate-to-severe cases in COVID-19, demonstrating COVID-19 infection affects coagulation activities.